1997
DOI: 10.1063/1.365983
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh strain and piezoelectric behavior in relaxor based ferroelectric single crystals

Abstract: The piezoelectric properties of relaxor based ferroelectric single crystals, such as Pb(Zn1/3Nb2/3)O3–PbTiO3 and Pb(Mg1/3Nb2/3)O3–PbTiO3 were investigated for electromechanical actuators. In contrast to polycrystalline materials such as Pb(Zr,Ti)O3, morphotropic phase boundary compositions were not essential for high piezoelectric strain. Piezoelectric coefficients (d33’s)>2500 pC/N and subsequent strain levels up to >0.6% with minimal hysteresis were observed. Crystallographically, high strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
2,322
5
15

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,910 publications
(2,464 citation statements)
references
References 12 publications
54
2,322
5
15
Order By: Relevance
“…An emerging trend is that magnetostriction enhancement in Fe based systems occurs for compositions near structural phase boundaries. An analogy with giant electrostriction of ferroelectric solid solution and relax ors 22,23 also points to the intriguing possibility that some structural boundaries in magnetic materials can act as property enhancing morphotropic phase boundaries. Indeed, Yang et al have reported a rhombohedral/tetragonal morphotropic phase boundary with enhanced magnetostrictive properties in the TbCo 2 -DyCo 2 sys tem occurring below 160 K (ref.…”
mentioning
confidence: 95%
“…An emerging trend is that magnetostriction enhancement in Fe based systems occurs for compositions near structural phase boundaries. An analogy with giant electrostriction of ferroelectric solid solution and relax ors 22,23 also points to the intriguing possibility that some structural boundaries in magnetic materials can act as property enhancing morphotropic phase boundaries. Indeed, Yang et al have reported a rhombohedral/tetragonal morphotropic phase boundary with enhanced magnetostrictive properties in the TbCo 2 -DyCo 2 sys tem occurring below 160 K (ref.…”
mentioning
confidence: 95%
“…The BEC tensor (zz component) of the Zn ion increases marginally from B1.93 to B2.04 (by 5.1%) upon the transition to the polar P6 3 mc structure from the nonpolar P6 3 /mmc structure. The enhanced BEC value of the P6 3 mc structure is strongly correlated with the ionic contribution to e 33 because the BEC is represented by the term (qP 3 /qu) e 3 in eqn (2). Thus, the Zn offcenter-dependent BEC tensor is expected to correlate well with the variation in the ionic contribution to e 33 .…”
Section: Resultsmentioning
confidence: 96%
“…[1][2][3] These characteristic properties are advantageous for applications for supercapacitors, and ultrasonic motors, piezoelectric boosters, medical ultrasonic probes, and so forth. 4,5) Most of the relaxor materials have a complex perovskitetype structure, which has a random or ordered arrangement of two B-site cations with different radii and ionic charges.…”
Section: Introductionmentioning
confidence: 99%